2002
DOI: 10.1117/12.481667
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of spectral degradation due to contaminant films on infrared and optical sensors

Abstract: Molecular surface contaminants can cause degradation of optical systems, especially if the contaminants exhibit strong absorption bands in the region of interest. Different strategies for estimation of spectral degradation responses due to uniform films for various types of systems are reviewed. One tool for calculating the effects of contaminant film thickness on signal degradation in the mid IR region is the simulation program CALCRT. The CALCRT database will be reviewed to correlate spectral n and k values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…In Figure 5, the relative detector responsivity degradation measured after 14 weeks of on-orbit operation shows good agreement with the infrared transmittance spectrum generated for 1 µm ice film using CALCRT. 17 The degradation profiles as a function of time were also qualitatively similar to CALCRT predictions based on a constant deposition rate. (One µm deposition in 14 weeks equates to an average local partial pressure of 6.7 x 10 -10 Torr, assuming water vapor at 200 K).…”
Section: Early On-orbit Resultssupporting
confidence: 62%
“…In Figure 5, the relative detector responsivity degradation measured after 14 weeks of on-orbit operation shows good agreement with the infrared transmittance spectrum generated for 1 µm ice film using CALCRT. 17 The degradation profiles as a function of time were also qualitatively similar to CALCRT predictions based on a constant deposition rate. (One µm deposition in 14 weeks equates to an average local partial pressure of 6.7 x 10 -10 Torr, assuming water vapor at 200 K).…”
Section: Early On-orbit Resultssupporting
confidence: 62%
“…The electron emission and transport properties of materials are key parameters in determining the likelihood of deleterious spacecraft charging effects [7,33,36,37] and are essential in modeling these effects with engineering tools such as the NASA NASCAP-2K [38][39][40], SPENVIS, and MUSCAT [41] codes. The SUSpECS studies of electron emission and resistivity will extend more than a decade of research in the field by the USU MPG [3,[6][7][8][9][10][11][12][13]19,40,[42][43]. Recent work [13,44] found that dissipation of charge accumulated on thin film insulating spacecraft surfaces during on-orbit conditions is substantially slower than predicted using resistivity values acquired by standard ASTM methods [45].…”
Section: B Electrical Properties Of Spacecraft Materialsmentioning
confidence: 99%
“…Synergistic phenomena in the space environment (e.g., charging, contamination, UV exposure, atomic oxygen) can cause dramatic changes in material surface properties and performance [3,47]. Thin contaminant layers readily change the optical [34,42,48] and electronic properties [15,16] of surfaces, and often result in long-term degradation of the optical, thermal control, or electronic performance of spacebased sensors and components.…”
Section: Charge-induced Contamination Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Stringent requirements for uniform work function of the FPMU probes led to coating key elements with Au [20]. Another critical concern is non-uniform modification of the Au work function due to external contamination or to diffusion of alloying materials from underlying layers into the Au, particularly at elevated temperatures [25]. A set of samples [Au, Au(2μm)/Ni(2μm) on 316 SS, Rh(2μm)/Ni(2μm) on 316 SS, Au(2μm)/Rh(2μm) on 316 SS, Au(2μm)/Rh(2μm)/Ni(2μm) on 316 SS] will be included in the unexposed samples on SUSpECS.…”
Section: Table I Suspecs Samplesmentioning
confidence: 99%